Densidade de sementes e estabelecimento de plântulas em restauração florestal via semeadura direta - Fernandes, Natiele Stephanie Rubio (Universidade Federal de São Carlos, 2024)
The successful establishment of native tree species in forest restoration projects via direct seeding is related to several factors, including the choice of species and seeding densities. This research aims to compare different densities in the establishment of tree species in order to establish an ideal minimum density for forest restoration via direct seeding considering a certain group of forest species. Seven forest species native to the Atlantic Forest in the state of São Paulo were selected: Croton floribundus Spreng, Guazuma ulmifolia Lam, Anadenanthera colubrina (Vell.) Brenan var. colubrina, Senegalia polyphylla (DC.) Britton & Rose, Copaifera langsdorffii Desf, Mimosa bimucronata (DC.) Kuntze and Hymenaea courbaril L., which were sown in an experimental area located in the municipality of Taubaté, SP, in the phytogeographic region of the Semideciduous Seasonal Forest. The experiment was conducted in a completely randomized block design, with four blocks and four sowing density treatments (20, 44, 89 and 178 of the seed mix per 37.5 m2 plot (7.5 m x 5.0 m), with the species grouped into three distinct groups: “very small seeds”, “small seeds” and “medium-large seeds”. The seeds were previously analyzed to determine the germination percentage. The seeds were sown in rows and the seedlings were assessed weekly for emergence and biweekly for height, diameter at ground surface and distance between individuals. One hundred and eighty days after sowing, we found that the number of established seedlings was higher at density four of 178 seeds per plot. With regard to height, there was a significant difference (p > 0.05) between the densities only in the last evaluation period (180 days), with an average of 19.22 cm for the treatment of 44 seeds by installments; 16.05 for the treatment of 89 seeds per plot and 15.32 for the treatment with the highest density. There was no significant difference for the diameter in any period. The species H. courbaril and S. polyphylla had the highest number of established seedlings. M. bimucronata had no emergent individuals. Based on the results, we conclude that the most suitable density within the evaluation of one hundred and eighty days is 44 seeds per plot.
Seed density and Seedling establishment in forest restoration via direct seeding
Keywords: Mata Atlântica; Atlantic forest; Densidade de plântulas; Seed density; Sustentabilidade; Sustainability; Manejo; Management; Reflorestamento; Reforestation; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::TECNOLOGIA E UTILIZACAO DE PRODUTOS FLORESTAIS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::FLORESTAMENTO E REFLORESTAMENTO; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::PROTECAO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::SEMENTES FLORESTAIS